Grendel's guide to love and war - Kaplan, A. E. (Alfred A. Knopf, 2017)
When a local bully upsets the senior community by throwing wild parties, an effort that is complicated by Aaron's PTSD and Tom's unrequited feelings for the bully's sister, misfit Tom and his friend Ed take matters into their own hands.